Aspecte i prefixació verbal en català antic - Bartra, Anna; Mateu, Jaume (Caplletra. Revista Internacional de Filologia, 2005)
The paper examines aspectual and selectional properties of Old Catalan prefixed verbs in comparison with their non prefixed counterparts. We ground our analysis on Talmy’s (1985, 2000) notion of verb framed and satellite framed languages and on Mateu (2002, 2003) and Mateu & Rigau (2002) theory of lexical structure, and we argue that telicity and other aspectual properties associated with prefixed verbs are by effects derived from the semantic value of the prefix together with the lexical structure they give rise to. Taking as a case in point the a- prefix of verbs such as «acórrer», we analyse the prefix as a path which relates a figure (the grammatical subject) to a ground (the argument introduced by a preposition) and which incorporates onto an abstract GO predicate conflating with the basic unergative predicate.